Konsep Cinta dalam Perspektif Erich Fromm sebagai Refleksi Menjalani Kehidupan Asmara - Arum Puspita Arini (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the concept of love in the perspective of Erich Fromm as a reflection of living a romantic life. This research uses a qualitative approach with the method of literature study and the use of literature review using various sources. The formal object of this research is Erich Fromm's theory of love, while the material object is the reflection of living a love life. The results and discussion show that the misunderstanding of the meaning of love which makes a love relationship not ideal, will make every individual who is in a love relationship suffer. So there is a need for an understanding of the concept of love in the perspective of Erich Fromm, which according to him love gives, understanding all manifestations and feelings of what lives in him, thus, will reflect a sense of happiness between partners. This research concludes that every individual who is in a romantic relationship, the nursery learns more about the true concept of love, which makes his love relationship healthy and ideal, not just craving love arbitrarily that dominates the entire life of his partner. This research recommends to all people who want and are currently living a love life to conduct a study of the concept of love according to Erich Fromm in order to make an ideal love life.